Electrolyte and application thereof
By adjusting the electrolyte composition and copolymer content, an electrolyte with high ionic conductivity at low temperatures and safety at high temperatures was achieved, solving the problems of low ionic conductivity and poor safety of solid-state batteries at low temperatures. It also provides reversible phase transition within the range of 20℃ to 70℃, reducing costs.
Patent Information
- Application Number
- CN202511477683.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-10-16
AI Technical Summary
Conventional electrolytes cannot simultaneously achieve both high-temperature safety and low-temperature ionic conductivity. Solid-state batteries pose safety risks at high temperatures and exhibit a significant decrease in ionic conductivity at low temperatures.
An electrolyte composed of alternating copolymers, a first solvent, a second solvent, a third solvent, lithium salts, and additives is used. By adjusting the copolymer content and solvent types, the electrolyte can achieve high ionic conductivity in a liquid state at low temperatures and undergo a phase transition to a solid state at high temperatures, thereby improving safety.
It achieves high ionic conductivity at low temperatures and safety at high temperatures, with adjustable phase change temperature, lower cost than ionic liquids, and reversible phase change of the electrolyte within the range of 20℃ to 70℃, preventing battery thermal runaway.
Smart Images

Figure CN120955216A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery technology, and more specifically, to an electrolyte and its application. Background Technology
[0002] Lithium-ion batteries have advantages such as high specific energy, lightweight, and long cycle life, and dominate applications in consumer electronics, new energy vehicles, and energy storage. Currently, the mainstream lithium batteries use organic solvents as electrolytes, which can lead to a series of safety issues in high-temperature environments, such as electrolyte decomposition and vaporization. Moreover, these electrolytes are flammable, which poses a serious safety challenge to liquid lithium-ion batteries in high-temperature environments.
[0003] Solid-state batteries are considered a solution to improve battery safety. They use non-flammable solid electrolytes instead of flammable organic solvents, significantly reducing safety hazards related to high-temperature thermal runaway and electrolyte combustion. In addition, solid-state batteries offer other advantages, such as the resistance of solid electrolytes to lithium dendrite formation, allowing them to be paired with lithium metal, which boasts an ultra-high theoretical specific capacity (3860 mAh / g), as the anode material. However, solid-state batteries face the challenge of significantly reduced ionic conductivity at low temperatures, a key bottleneck restricting their application in cold environments. For example, the ionic conductivity of sulfide solid electrolytes is only 0.1~0.2 ms / cm at -20℃.
[0004] In view of this, the present invention is hereby proposed. Summary of the Invention
[0005] The primary objective of this invention is to provide an electrolyte that addresses the technical shortcomings of conventional electrolytes in simultaneously achieving high-temperature safety and low-temperature ionic conductivity.
[0006] The second objective of this invention is to provide a secondary battery.
[0007] A third objective of this invention is to provide an electrical device.
[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: An electrolyte comprising an alternating copolymer, a first solvent, a second solvent, a third solvent, a lithium salt, and an additive; The alternating copolymer is obtained by polymerization of a first monomer and a second monomer; The first monomer comprises a terminal alkenyl group, a terminal halogen atom, and an ether bond, and the second monomer comprises at least one of maleic anhydride, citraconic anhydride, itaconic anhydride, maleimide, and 2,5-thiophenedione.
[0009] In one embodiment, the degree of polymerization of the alternating copolymer is 10,000 to 60,000.
[0010] In one embodiment, the content of the alternating copolymer in the electrolyte is 6 wt.% to 24 wt.%.
[0011] In one embodiment, the first monomer comprises at least one of the following compounds (I) to (VIII): (I); (II); (III); (IV); (V); (VI); (VII); (VIII).
[0012] In one embodiment, the first solvent includes at least one selected from ethyl propionate, propyl acetate, methyl acetate, ethyl butyrate, butyl acetate, tetrahydrofuran, dimethoxyethane, N,N-dimethylformamide, and dimethyl sulfoxide.
[0013] In one embodiment, the content of the first solvent in the electrolyte is 50 wt.% to 70 wt.%.
[0014] In one embodiment, the second solvent is an alkane compound, and the alkane compound includes at least one of n-octane, n-heptane, n-hexane, and cyclohexane.
[0015] In one embodiment, the content of the second solvent in the electrolyte is 5 wt.% to 10 wt.%.
[0016] In one embodiment, the third solvent is an amphiphilic solvent, which includes at least one of the following compounds (a) to (e): (a); (b); (c); (d); (e); R-based is -C n H 2n+1 n is independently selected from 4 to 8.
[0017] In one embodiment, the content of the third solvent in the electrolyte is 5 wt.% to 10 wt.%.
[0018] In one embodiment, the lithium salt includes at least one of LiPF6, LiBF4, LiFSI, LiTFSI, LiAsF6, LiBOB, LiCF3SO3, and LiClO4.
[0019] In one embodiment, the lithium salt content in the electrolyte is 5 wt.% to 15 wt.%.
[0020] In one embodiment, the additive comprises at least one of the following compounds (A) to (D): (A); (B); (C); (D).
[0021] In one embodiment, the additive content in the electrolyte is 1 wt.% to 3 wt.%.
[0022] A secondary battery comprising the electrolyte.
[0023] An electrical device includes the aforementioned secondary battery.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides an electrolyte material capable of undergoing a reversible phase transition in an organic solvent, which exhibits both high-temperature safety and high low-temperature ionic conductivity. The electrolyte comprises a specific alternating copolymer as the phase transition polymer material, three solvents, a lithium salt, and other additives. The electrolyte is liquid at low temperatures, exhibiting high ionic conductivity similar to an electrolyte solution. As the temperature increases, the electrolyte undergoes a reversible phase transition to a solid state, demonstrating safety and stability at high temperatures.
[0025] (1) High ionic conductivity at low temperature: By adjusting the content of alternating copolymers, the content of amphiphilic solvents, and the types and contents of additives, the electrolyte of the present invention can achieve a high ionic conductivity at low temperature, which is 5 to 10 times that of conventional sulfide solid electrolytes.
[0026] (2) High temperature safety: When the lithium battery using the electrolyte of the present invention is in the normal operating temperature range of 20°C to 30°C, the electrolyte is in a liquid state; when the battery temperature rises, the electrolyte undergoes a phase change, and the phase change temperature is between 20°C and 70°C. The phase change temperature range has not yet reached the decomposition temperature of the SEI film. After the phase change occurs, the battery capacity decreases, which slows down the continued rise of the battery temperature and prevents the battery from thermal runaway.
[0027] (3) Low cost: Existing temperature phase change electrolytes usually use ionic liquids as carriers, which are expensive. For example, the cost of imidazole ionic liquids is as high as 500~1500 yuan / kg. In contrast, the present invention uses low-cost organic solvents to achieve a wide temperature range phase change of electrolytes from 20℃ to 70℃. Compared with ionic liquids, the present invention has a much lower cost while maintaining similar performance. Attached Figure Description
[0028] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0029] Figure 1 These are cycle capacity performance diagrams for various embodiments of the present invention; Figure 2 This is a transmittance result diagram of Example 1 of the present invention. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. In addition, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0031] A first aspect of the present invention is to provide an electrolyte.
[0032] The electrolyte of the present invention comprises an alternating copolymer, a first solvent, a second solvent, a third solvent, a lithium salt, and an additive; wherein the alternating copolymer is obtained by polymerization of a first monomer and a second monomer; the first monomer comprises a terminal alkenyl group, a terminal halogen atom, and an ether bond, and the second monomer comprises at least one of maleic anhydride, citraconic anhydride, itaconic anhydride, maleimide, and 2,5-thiophenedione.
[0033] The alternating copolymer described in this invention primarily satisfies the conventional definition in the art, namely, that the two monomer units in the macromolecular chain are arranged in a strictly alternating manner, and must meet the conditions of containing only two monomers, at least one monomer being unable to homopolymerize, and heteropolymer copolymerization being necessary; in this invention, the alternating copolymer is obtained by alternating polymerization of the first monomer and the second monomer.
[0034] In this invention, the structure of the second monomer satisfies the conventional definition of a compound whose name implies it. Specifically, the structural formula of maleic anhydride is: The structural formula of citric acid anhydride is: The structural formula of itaconic anhydride is: The structural formula of maleimide is: The structural formula of 2,5-thiophenedionone is: .
[0035] In a preferred embodiment, the degree of polymerization of the alternating copolymer is 10,000 to 60,000, including but not limited to 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 (×10⁻⁶). 4 The range of values formed by any one or any two of the following.
[0036] In a preferred embodiment, the terminal halogen atom in the first monomer is at least one of a fluorine atom or a chlorine atom.
[0037] In a more preferred embodiment, the first monomer comprises at least one of the following compounds (I) to (VIII): (I); (II); (III); (IV); (V); (VI); (VII); (VIII).
[0038] In a preferred embodiment, the content of the alternating copolymer in the electrolyte is 6 wt.% to 24 wt.%, including but not limited to any one or any two of the following values: 6, 8, 10, 12, 15, 16, 18, 20, 22, 23, and 24 (wt.%).
[0039] In a preferred embodiment, the first solvent is a major dispersing solvent for the electrolyte, and the first solvent includes, but is not limited to, at least one of ethyl propionate, propyl acetate, methyl acetate, ethyl butyrate, butyl acetate, tetrahydrofuran, dimethoxyethane, N,N-dimethylformamide, and dimethyl sulfoxide.
[0040] In a preferred embodiment, the content of the first solvent in the electrolyte is 50 wt.% to 70 wt.%, including but not limited to any one or any two of the following values: 50, 52, 54, 55, 56, 58, 60, 62, 64, 65, 66, 68, and 70 (wt.%).
[0041] In a preferred embodiment, the second solvent is an alkane compound, and the alkane compound includes at least one of n-octane, n-heptane, n-hexane, and cyclohexane.
[0042] In a preferred embodiment, the content of the second solvent in the electrolyte is 5 wt.% to 10 wt.%, including but not limited to any one or any two of the following: 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 (wt.%).
[0043] In a preferred embodiment, the third solvent is an amphiphilic solvent, that is, a special solvent having hydrophilic (polar) and lipophilic (nonpolar) groups; the amphiphilic solvent includes both alkyl and ester groups.
[0044] In a more preferred embodiment, the amphiphilic solvent comprises at least one of the following compounds (a) to (e): (a); (b); (c); (d); (e); Furthermore, in compounds (a) to (e), the R group is -C. n H 2n+1 n is independently selected from 4 to 8.
[0045] In a preferred embodiment, the content of the third solvent in the electrolyte is 5 wt.% to 10 wt.%, including but not limited to any one or any two of the following: 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, and 10 (wt.%).
[0046] It is worth noting that three solvents are used in this invention. The first solvent is a commonly used solvent in lithium battery electrolytes, mainly esters and ethers. The second solvent can produce the LCST phenomenon with the alternating copolymer, that is, the alternating copolymer dissolves as a phase change polymer at low temperatures and precipitates at high temperatures. The third solvent is a co-solvent, which is amphiphilic and can improve the solubility between the first and second solvents. Specifically, the second solvent contains alkanes, which have very low polarity, which is significantly different from the polarity of the esters in the first solvent. This invention solves the compatibility problem between the first and second solvents by adding the third solvent as a co-solvent.
[0047] Furthermore, regarding the aforementioned LCST (Lower Critical Solution Temperature) phenomenon, the following extended explanation was found: At lower temperatures, hydrogen bonds form between the molecules of the alternating copolymer and the second solvent, and the alternating copolymer molecules dissolve in the second solvent in a chain-like manner. As the temperature increases, the enthalpy change of the hydrogen bond breaking between the alternating copolymer and the second solvent molecules is an enthalpy increase, causing the alternating copolymer to precipitate from the second solvent. The entropy change of the entire electrolyte system is an entropy increase, and this entropy increase dominates as the temperature rises. According to ΔG = ΔH - TΔS, ΔG < 0, and the reaction of the alternating copolymer precipitating from the second solvent proceeds spontaneously. The effect is that the alternating copolymer precipitates into agglomerates, and the entire system changes from a liquid to a solid state.
[0048] In a preferred embodiment, the lithium salt includes at least one of LiPF6, LiBF4, LiFSI, LiTFSI, LiAsF6, LiBOB, LiCF3SO3, and LiClO4.
[0049] In a preferred embodiment, the lithium salt content in the electrolyte is 5 wt.% to 15 wt.%, including but not limited to any one or any two of the following values: 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, and 15 (wt.%).
[0050] In a preferred embodiment, the additive includes at least one of the following compounds (A) to (D): (A); (B); (C); (D).
[0051] In a preferred embodiment, the content of the additive in the electrolyte is 1 wt.% to 3 wt.%, including but not limited to any one or any two of the following (wt.%): 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, and 3 (wt.%).
[0052] In a preferred embodiment, the electrolyte can undergo a reversible phase transition depending on the temperature, and the phase transition temperature of the electrolyte is 20℃~70℃. Testing has shown that the electrolyte of the present invention has good phase transition reversibility and can achieve at least 100 reversible cycles within the above temperature range.
[0053] It is worth noting that the phase transition temperature window of the electrolyte described in this invention is adjustable; the phase transition temperature can be controlled by adjusting the type, content and molecular weight of the first and second monomers, the type and content of the second solvent, and the type and content of the third solvent.
[0054] As a preferred embodiment, the preparation method of the alternating copolymer includes the following steps: stirring the first monomer, the second monomer, the initiator and the reaction solvent at 50°C to 100°C for 1 h to 6 h, and then separating and drying the precursor of the alternating copolymer in a poor solvent to obtain the alternating copolymer.
[0055] As an optional implementation, the drying is vacuum drying at a temperature of 80℃~120℃ for 6h~10h.
[0056] In a more preferred embodiment, the molar ratio of the first monomer to the second monomer is 1:1; the total molar amount is the sum of the molar amounts of the first monomer and the second monomer; the molar ratio of the initiator to the total molar amount is 1:(100~1000); and the molar ratio of the reaction solvent to the total molar amount is (5~15):1.
[0057] In a more preferred embodiment, the initiator includes at least one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), and benzoyl peroxide (BPO); the reaction solvent includes at least one of methyl ethyl ketone, ethyl acetate, acetone, and toluene; in another more preferred embodiment, the undesirable solvent includes at least one of diethyl ether, n-hexane, and petroleum ether, and the amount of the undesirable solvent is determined by the complete precipitation of the precursor of the alternating copolymer, and those skilled in the art can adjust the amount accordingly.
[0058] In a preferred embodiment, the preparation method of the electrolyte includes the following steps: thoroughly mixing the alternating copolymer, the first solvent, the second solvent, the third solvent, the lithium salt, and the additives to obtain the electrolyte.
[0059] As an optional implementation method, the thorough mixing can be assisted by means of oscillation, stirring, shaking, centrifugation, ultrasound, heating, etc., which helps to accelerate dispersion and obtain a relatively uniform dispersion system.
[0060] A second aspect of the present invention is to provide a secondary battery comprising an electrolyte as described in the first aspect.
[0061] In a preferred embodiment, the secondary battery is a lithium-ion battery.
[0062] In a more preferred embodiment, the positive electrode of the lithium-ion battery comprises one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, or ternary materials, and the negative electrode comprises one of natural graphite, artificial graphite, silicon, silicon-carbon composite material, or metallic lithium. In some optional embodiments, the separator of the lithium-ion battery comprises one of polyethylene, polypropylene, polyimide, polyamide, polyvinylidene fluoride, or polytetrafluoroethylene.
[0063] A third aspect of the present invention is to provide an electrical device comprising a secondary battery as described in the second aspect.
[0064] It is understood that the electrical equipment can be any kind of equipment or device that relies on electrical energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc.; when the secondary battery is included, any electrical equipment equipped with the secondary battery can be an embodiment of the present invention.
[0065] Examples 1-9 S1. The first monomer, the second monomer, the initiator, and the reaction solvent are stirred at a specific temperature for a specific time to ensure that the molar ratio between the two monomers is 1:1. The total molar amount is the sum of the molar amounts of the two monomers, the ratio of the molar amount of the initiator to the total molar amount is the M value, and the ratio of the molar amount of the reaction solvent to the total molar amount is the N value. After the polymerization reaction is completed, a poor solvent is added to the reaction system, and after stirring, precipitation and centrifugation are performed to obtain a solid phase. Then, the solid phase is dried under vacuum at 100°C for 8 hours to obtain the alternating copolymer of this embodiment.
[0066] In each embodiment, the reaction temperature, reaction time, M and N values, initiator type, reaction solvent type, and unsuitable solvent type are recorded in Table 1; in addition, the types of each monomer are recorded in Table 2 below.
[0067] S2. In an argon-filled glove box, the alternating copolymer (obtained by alternating polymerization of the first monomer and the second monomer), the first solvent, the second solvent, the third solvent, the lithium salt, and the additives are mixed and placed on a stirring device and stirred at 800 rpm for 30 min to obtain the electrolytes of each embodiment.
[0068] In each embodiment, the types of monomers, the degree of polymerization of the alternating copolymers, the amount of alternating copolymers, the types and amounts of solvents, the types and amounts of lithium salts, and the types and amounts of additives are all described in Table 1. It is worth noting that the specific substances referred to by compounds (I)~(VIII), (a)~(e), and (A)~(D) in Table 2 are consistent with the serial numbers described in the specification of this invention; for compounds (a)~(e), there exists an R group with -C n H 2n+1 Table 2 provides the n values, and the two R groups of compound (e) have the same n value.
[0069] Table 1
[0070] Table 2
[0071] Comparative Example 1: Basically the same as Example 1, except that: no alternating copolymer was added, and the content of the first solvent was changed to 73 wt.%.
[0072] Comparative Example 2: Basically the same as Example 3, except that the alternating copolymer is replaced by a self-polymer of the first monomer.
[0073] Comparative Example 3: Basically the same as Example 3, except that: no second solvent is added, and the content of the first solvent is changed to 72 wt.%. Comparative Example 4: Basically the same as Example 3, except that no third solvent is added and the content of the first solvent is changed to 72 wt.%.
[0074] Test case (1) Ionic conductivity test: A 2cm² area was used as the test site. 2 A battery is assembled from a stainless steel gasket and an electrolyte. The battery is placed in a low-temperature test chamber at -20°C for 3 hours. Then, it is connected to an electrochemical workstation. The electrochemical workstation applies a sinusoidal voltage signal with an amplitude of 20 mV and a test frequency range of 4 MHz to 100 MHz. The resistance of the electrolyte is recorded and the ionic conductivity is calculated.
[0075] (2) Discharge capacity test: The electrolytes obtained from each example and the comparative example were used to prepare test batteries; specifically, lithium iron phosphate was used as the positive electrode, lithium metal was used as the negative electrode, and polyvinylidene fluoride was used as the separator. The batteries were assembled into the battery casing to obtain the corresponding lithium batteries for each example.
[0076] Each assembled battery was placed in a high and low temperature test chamber at 25°C and left to stand for 1 hour. Then, it was connected to a charge / discharge apparatus and discharged at a rate of 0.2 C with a discharge cutoff voltage of 2 V. The capacity of the first discharge at 25°C was recorded (corresponding to...). Figure 1 The capacity value was recorded when the number of cycles was 1. The battery was then placed in a temperature chamber, which was raised from the ambient temperature to 75°C at a rate of 5°C / min and maintained at this temperature for 30 minutes. The chamber was then cooled to 25°C at a rate of 1°C / min and maintained at this temperature for 30 minutes. The battery was then discharged at a rate of 0.2 C, with a discharge cutoff voltage of 2 V. The discharge capacity was recorded (corresponding to...). Figure 1 (The capacity value when the number of loops is 2). Repeat the above steps until 5 loops are generated, and plot the results. Figure 1 The capacity performance diagram shown.
[0077] (3) Phase transition temperature test: The phase transition temperature of the electrolyte is determined by measuring the transmittance of the electrolyte solution; the transmittance of the electrolyte solution is measured using a variable temperature ultraviolet-visible spectrometer; the solution is placed on the heating stage of the instrument and heated at a heating rate of 1℃ / min, and the transmittance curve is recorded. The temperature at which the transmittance reaches 0 is defined as the phase transition temperature.
[0078] (4) Phase transition reversibility test: The transmittance of each electrolyte was tested at 25℃. When the transmittance was 100%, the phase was liquid. The reagent bottle containing the electrolyte was placed on a heating platform, the heating temperature was set to 70℃, the heating rate was 20℃ / min, and it was kept at 70℃ for 10 minutes. The transmittance was then tested. When the transmittance was <5%, the phase was solid. The heater was turned off and the electrolyte was cooled to 25℃. This was recorded as one cycle. A total of 100 cycles were performed. After 100 cycles, the transmittance of the electrolyte material was required to be 100% at 25℃ and <5% at 70℃. This proved that the electrolyte was reversible. Otherwise, it was irreversible.
[0079] Figure 2 A transmittance graph of the electrolyte corresponding to Example 1 is provided after 100 cycles.
[0080] The results of the above experiments (1) to (4) are recorded in Table 3 below.
[0081] Table 3
[0082] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.
Claims
1. An electrolyte, characterized in that, The electrolyte comprises an alternating copolymer, a first solvent, a second solvent, a third solvent, a lithium salt, and additives; The alternating copolymer is obtained by polymerization of a first monomer and a second monomer; The first monomer comprises a terminal alkenyl group, a terminal halogen atom, and an ether bond, and the second monomer comprises at least one of maleic anhydride, citraconic anhydride, itaconic anhydride, maleimide, and 2,5-thiophenedione.
2. The electrolyte according to claim 1, characterized in that, The degree of polymerization of the alternating copolymer is 10,000 to 60,000; And / or, in the electrolyte, the content of the alternating copolymer is 6 wt.% to 24 wt.%.
3. The electrolyte according to claim 1, characterized in that, The first monomer comprises at least one of the following compounds (I) to (VIII): (AND); (II); (III)) (IV)) (V); (VI); (VII)? (VIII)。 4. The electrolyte according to claim 1, characterized in that, The first solvent includes at least one of ethyl propionate, propyl acetate, methyl acetate, ethyl butyrate, butyl acetate, tetrahydrofuran, dimethoxyethane, N,N-dimethylformamide, and dimethyl sulfoxide. And / or, in the electrolyte, the content of the first solvent is 50 wt.% to 70 wt.%.
5. The electrolyte according to claim 1, characterized in that, The second solvent is an alkane compound, and the alkane compound includes at least one of n-octane, n-heptane, n-hexane, and cyclohexane; And / or, in the electrolyte, the content of the second solvent is 5 wt.% to 10 wt.%.
6. The electrolyte according to claim 1, characterized in that, The third solvent is an amphiphilic solvent, which includes at least one of the following compounds (a) to (e): (a); (b); (c); (d); (e); R-based is -C n H 2n+1 n is independently selected from 4 to 8; And / or, in the electrolyte, the content of the third solvent is 5 wt.% to 10 wt.%.
7. The electrolyte according to claim 1, characterized in that, The lithium salt includes at least one of LiPF6, LiBF4, LiFSI, LiTFSI, LiAsF6, LiBOB, LiCF3SO3, and LiClO4; And / or, in the electrolyte, the lithium salt content is 5 wt.% to 15 wt.%.
8. The electrolyte according to claim 1, characterized in that, The additive includes at least one of the following compounds (A) to (D): (A); (B); (C); (D); And / or, in the electrolyte, the content of the additive is 1 wt.% to 3 wt.%.
9. A secondary battery, characterized in that, Includes the electrolyte as described in any one of claims 1 to 8.
10. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 9.
Citation Information
Patent Citations
Preparation and application of gel polymer electrolyte
CN108336403A
Composition for preparing positive electrode of secondary battery, and positive electrode for secondary battery and secondary battery prepared using the same
KR1020170111749A
High ionic conductivity gel polymer electrolyte for rechargeble polymber secondary battery
US20070141461A1
Fluorine-containing binder
WO2010134465A1
Electrolyte and lithium ion battery
WO2017152624A1
Cited By
Electrolyte and battery comprising same
CN122267304A